The Cost of Preterm Birth Throughout Childhood in England and Wales - Mangham, L; Petrou, S; Doyle, L; Draper, E; Marlow, N (American Academy of Pediatrics, 2009)
Infants born preterm are at increased risk of adverse health and developmental outcomes. Mortality and morbidity after preterm birth impose a burden on finite public sector resources. This study considers the economic consequences of preterm birth from birth to adult life and compares the costs accruing to those born preterm with those born at term.A decision-analytic model was constructed to estimate the costs to the public sector over the first 18 years after birth, stratified by week of gestational age at birth. Costs were discounted and reported in UK pounds at 2006 prices. Probabilistic sensitivity analysis was used to examine uncertainty in the model parameters and generate confidence intervals surrounding the cost estimates.The model estimates the costs associated with a hypothetical cohort of 669601 children and is based on live birth and preterm birth data from England and Wales in 2006. The total cost of preterm birth to the public sector was estimated to be pound2.946 billion (US $4.567 billion), and an inverse relationship was identified between gestational age at birth and the average public sector cost per surviving child. The incremental cost per preterm child surviving to 18 years compared with a term survivor was estimated at pound22885 (US $35471). The corresponding estimates for a very and extremely preterm child were substantially higher at pound61781 (US $95760) and pound94740 (US $146847), respectively.Despite concerns about ongoing costs after discharge from perinatal services, the largest contribution to the economic implications of preterm birth are hospital inpatient costs after birth, which are responsible for 92.0% of the incremental costs per preterm survivor.